Ответ(ы) на вопрос:
[latex]F(x)=(15-2x- x^{2} )(2x+ \frac{2}{x} - \frac{1}{ x^{2} } ) \\ F'(x)=(-2-2x)(2x+ \frac{2}{x} - \frac{1}{ x^{2} } )+(15-2x- x^{2} )(2- \frac{2}{ x^{2} }+ \frac{2}{ x^{3} } )=[/latex][latex]-4x- \frac{4}{x} + \frac{2}{ x^{2} } -4 x^{2} -4 + \frac{2}{ x } +30- \frac{30}{ x^{2} } + \frac{30}{ x^{3} } -4x+ \frac{4}{ x } - \frac{4}{ x^{2} }-2 x^{2} +2-[/latex][latex] \frac{2}{x} =[/latex][latex]\frac{30}{ x^{3} }-\frac{32}{ x^{2} } -6 x^{2}-8x +28 [/latex]
Не нашли ответ?
Похожие вопросы